Fabrication of Hierarchical Potassium Titanium Phosphate Spheroids: A Host Material for Sodium‐Ion and Potassium‐Ion Storage. Issue 27 (6th August 2018) - Wei, Zhixuan; Wang, Dongxue; Li, Malin; Gao, Yu; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract: Identifying suitable electrode materials for sodium‐ion and potassium‐ion storage holds the key to the development of earth‐abundant energy‐storage technologies. This study reports an anode material based on self‐assembled hierarchical spheroid‐like KTi2 (PO4 )3 @C nanocomposites synthesized via an electrospray method. Such an architecture synergistically combines the advantages of the conductive carbon network and allows sufficient space for the infiltration of the electrolyte from the porous structure, leading to an impressive electrochemical performance, as reflected by the high reversible capacity (283.7 mA h g −1 for Na‐ion batteries; 292.7 mA h g −1 for K‐ion batteries) and superior rate capability (136.1 mA h g −1 at 10 A g −1 for Na‐ion batteries; 133.1 mA h g −1 at 1 A g −1 for K‐ion batteries) of the resulting material. Moreover, the different ion diffusion behaviors in the two systems are revealed to account for the difference in rate performance. These findings suggest that KTi2 (PO4 )3 @C is a promising candidate as an anode material for sodium‐ion and potassium‐ion batteries. In particular, the present synthetic approach could be extended to other functional electrode materials for energy‐storage materials. Abstract : This image shows an illustration of KTP@C as a high‐performance anode for sodium/potassium ion batteries, with a high rate performance of 136.1 mA h g −1 at 10 A g −1 for sodium ion batteries and 133.1 mA h g −1 at 1 A g −1 for potassium ion batteries. In addition, the different ion diffusion behaviors account for the difference in rate performance.